The Symbols of Gender-Stereotype in Hans Christian Andersenâ€™s the Little Mermaid - Jepri Ali Saiful; Ari Setyorini (Tell : Teaching of English Language and Literature Journal, 2015)
It is seen that there is an existence of gender-stereotype that unwittingly occurred in children's literature. The gender-stereotype of how man and woman should be and behave considering on his/her proper activities in a real life might be portrayed throughout the symbolizations in which numerous readers do not understand what they are about, whereas those symbols of gender-stereotype are teaching the children the concept of masculinity and femininity. This study thus scrutinizes the symbols of gender-stereotype in Hans Christian Andersenâ€Ÿs The Little Mermaid. The data analysis is in the form of symbols which have the issues of gender-stereotype taken from the original fairy tale of The Little Mermaid in 1836. The aims of this study are to find out the symbols of gender-stereotype and describe the meaning of each symbol. Utilizing descriptive qualitative method, the results of this study are the symbols which have the gender-stereotype of masculinity are â€œKingâ€ related to non-emotional and intellectuality in authority of a man. â€œKnifeâ€ is found allied to the masculinity trait of a strong man and â€œSwordâ€ is an analogue of a brave, adventurous and intellectual man. Moreover, the symbols of femininity found are the â€œMermaid or Sirenâ€ is interwoven to such the embodiment of a flirtatious woman. â€œLong Hairâ€ is germane to a loyal and submissive woman. The last, â€œOysterâ€ is represented as a nurturing woman. Keywords: Symbol, Gender-Stereotype, The Little Mermaid